CHF5074 (CSP-1103) induces microglia alternative activation in plaque-free Tg2576 mice and primary glial cultures exposed to beta-amyloid. (27th August 2015) - Porrini, V.; Lanzillotta, A.; Branca, C.; Benarese, M.; Parrella, E.; Lorenzini, L.; Calzà, L.; Flaibani, R.; Spano, P.F.; Imbimbo, B.P.; Pizzi, M.
Highlights: CHF5074 enhances expression of phagocytic "M2" microglia markers in youngTg2576 mice. CHF5074 polarizes microglia from M1 to M2 phenotype in Aβ-treated cultures. As a microglia modulator, CHF5074 may represent an innovative strategy in AD therapy. Abstract: Activation of microglia associated with neuroinflammation and loss of phagocytic activity is considered to play a prominent role in the pathogenesis of Alzheimer's disease (AD). CHF5074 (CSP-1103) has been shown to improve cognition and reduce brain inflammation in patients with mild cognitive impairment (MCI). CHF5074 was also found to reverse impairments in recognition memory and improve hippocampal long-term potentiation when administered to plaque-free Tg2576 mice (5-month-old) for 4 weeks. Though, no investigation has focused on the consequence of CHF5074 treatment on microglia polarization yet. In this study we evaluated the effect of CHF5074 administration (375 ppm in the diet) to 5-month-old Tg2576 mice on the expression of pro-inflammatory (M1) genes, Interleukin 1 beta (IL-1β), Tumor Necrosis Factor alpha (TNFα) and inducible Nitric Oxide Synthase (iNOS), and anti-inflammatory/phagocytic (M2) markers Mannose Receptor type C 1 (MRC1/CD206), Triggering Receptor Expressed on Myeloid cells 2 (TREM2) and Chitinase 3-like 3 (Ym1). No changes of pro-inflammatory gene transcription but a reduced expression of MRC1/CD206, TREM2 and Ym1 were detected in the hippocampus of young Tg2576 mice receiving normal diet, when compared to wild-type littermates. CHF5074 did not affect the pro-inflammatory transcription but significantly increased the expression of MRC1/CD206 and Ym1. CHF5074 effects appeared to be hippocampus-specific, as the M2 transcripts were only slightly modified in the cerebral cortex. In primary cultures of mouse astrocyte-microglia, CHF5074 totally suppressed the expression of TNF-α, IL-1β and iNOS induced by 10 μM β-amyloid1 – 42 (Aβ42 ). Moreover, CHF5074 significantly increased the expression of anti-inflammatory/phagocytic markers MRC1/CD206 and TREM2, reduced by the Aβ42 application alone. The effect of CHF5074 was not reproduced by ibuprofen (3 μM or 500 μM) or R-flurbiprofen (3 μM or 100 μM), as both compounds limited the pro-inflammatory gene expression but did not modify the anti-inflammatory/phagocytic transcription. These data show that CHF5074 specifically drives the expression of microglia M2 markers either in young Tg2576 hippocampus or in primary astrocyte-microglia cultures, suggesting its potential therapeutic efficacy as microglial modulator in the early phase of AD.